THE EFFECT OF SUPERVISIOR AND COMPENSATION ON EMPLOYEE JOB SATISFACTION OF PT KARYA MANUNGGAL JATI - Maulidiyah, Miftah Aulia; Kustini, Kustini (Yayasan Education and Social Center, 2023)
This study aims to determine the effect of supervision and compensation on job satisfaction of PT Karya Manunggal Jati employees. This type of research uses quantitative descriptive. The population in this study were all employees of PT Karya Manunggal Jati in Sidoarjo City. The number of samples used in this study were 57 respondents with the sampling technique using the slovin technique. The research instrument used a questionnaire with google form and used Partial Least Square (PLS) analysis tools. The analysis technique includes validity test, reliability test, and hypothesis testing. The results in this study indicate that supervision and compensation have a positive and significant effect on employee job satisfaction